PENGARUH PENGGUNAAN METODE PEMBELAJARAN PENEMUAN (DISCOVERY LEARNING) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA NEGERI 1 GARAWANGI - Lutfi Rohmawati (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2019)
The purpose of this study was to determine the discovery learning method (Discovery Learning) can result in students' critical thinking is higher than the lecture method. To determine the increase in students' critical thinking skills by using the discovery learning method (Discovery Learning) is higher than the lecture method. The results showed that the pretest results on students' critical thinking skills between the experimental class and the control class before learning rate has the same critical thinking skills. The first hypothesis discovery learning method (Discovery Learning) can result in students 'critical thinking is higher than the lecture method is accepted, meaning that after learning with the use of discovery learning methods (Discovery Learning) students' critical thinking skills higher than the lecture method. As for the Improvement of students' critical thinking skills by using the discovery learning method (Discovery Learning) is higher than the lecture method. This means that the second hypothesis is accepted. Thus there is an increase in critical thinking skills of students in the experimental class higher than the control class. From the above evidence, the discovery learning method (Discovery Learning) can be used as an alternative in economic learning in improving students' critical thinking skills.